PENGGUNAAN SLIMS 9.4.2 PADA RUMAH BACA ANAK NAGARI DALAM MEMUDAHKAN TEMU KEMBALI INFORMASI - Nabila, Dinda; Rukmana, Evi Nursanti; Rohman, Asep Saeful (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
Rapid advances in technology are making it more convenient for the various activities currently being carried out. Technology that continues to develop requires humans to be able to follow these developments. The Nagari Children's Reading House is one of the agencies that has developed an automation system as an application of this technology. The purpose of this study was to analyze the use of the Senayan Library Management System (SLiMS) at Rumah Baca Anak Nagari and to assist in data entry into SLiMS. This study uses descriptive qualitative research methods. The Nagari Children's Reading House has used SLiMS which they learned self-taught and from training held by the library. By using SLiMS, they are able to arrange books on the shelves according to their classification numbers and can make it easier to find books in this reading house.